HASIL KERJA MINIMAL BERBASIS WAKTU SEBAGAI STRATEGI PENILAIAN KINERJA FUNGSIONAL PERENCANA - kunkun Kobul Kurniawan (Journal Of Regional Public Administration (JRPA), 2021)
Within equalization for administrative positions into function positions, especially planners, various efforts must be improved performance. Time-Based Minimal Work Results (HKMBW) is one of the planner's performance appraisal strategies. HKMBW refers to the minimum cumulative credit score each year, which is 25 credit points. Currently, the Employee Performance Target (SKP) is the reference for evaluating the performance of function positions, so the planners are obliged to include HKMBW in the Employee Performance Target (SKP) as one of the implementation requirements every year.